High temperature oxidation of iron-chromium alloys - 430260 Astuty Amrin; Ali Ourdjini; Stott, F. H.; Scientific Conference [of] Electron Microscopy Society Malaysia (8th : 1999 : Pahang) (Skudai : Universiti Teknologi Malaysia, 1999)
09